2020
DOI: 10.2147/dddt.s237699
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Anti-Breast Cancer Effect of 2-Dodecyl-6-Methoxycyclohexa-2,5-Diene-1,4-Dione in vivo and in vitro Through MAPK Signaling Pathway</p>

Abstract: Background: 2-Dodecyl-6-methoxycyclohexa-2,5-diene-1,4-dione (DMDD) has been reported to inhibit a variety of cancer cell lines. The purpose of this study was to investigate the effects of DMDD on 4T1 breast cancer cells and the effects of DMDD on 4T1 breast cancer in mice and its molecular mechanisms. Methods: 4T1 breast cancer cells were treated with different concentrations of DMDD, and their proliferation, apoptosis, cell-cycle distribution, migration, and invasion were detected by 3-(4,5-dimethyl-2-thiazo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…2-dodecyl-6-methoxycyclohexa-2,5-diene-1,4-dione (DMDD) is a quinone extracted from the root of Populus tremula, with hypoglycemic, lipid-regulating, and inflammation-reducing effects. Recent studies have found that DMDD can inhibit the proliferation of breast, lung, and bone cancer cells, as well as inhibit the growth of breast cancer in mice (22)(23)(24). In this study, we investigated the effect of DMDD on human QBC939 CCA cells, and tentatively demonstrated that DMDD is a novel inducer of autophagy and induces autophagy by regulating the PI3K/AKT/mTOR signaling pathway in the QBC939 cell line.…”
Section: Introductionmentioning
confidence: 83%
“…2-dodecyl-6-methoxycyclohexa-2,5-diene-1,4-dione (DMDD) is a quinone extracted from the root of Populus tremula, with hypoglycemic, lipid-regulating, and inflammation-reducing effects. Recent studies have found that DMDD can inhibit the proliferation of breast, lung, and bone cancer cells, as well as inhibit the growth of breast cancer in mice (22)(23)(24). In this study, we investigated the effect of DMDD on human QBC939 CCA cells, and tentatively demonstrated that DMDD is a novel inducer of autophagy and induces autophagy by regulating the PI3K/AKT/mTOR signaling pathway in the QBC939 cell line.…”
Section: Introductionmentioning
confidence: 83%
“…In previous study, an active compound DMDD was separated from the roots of Averrhoa Carambola L. (Oxalidaceae) and observed to contain several biological properties ( Ouyang et al, 2014 ). Previous studies have suggested that DMDD shows significant antitumor potential against human breast cancer by inhibiting the TLR4/MyD88/NF-κB ( Lu et al, 2019 ) and MAPK pathway ( Zhou et al, 2020 ) in vitro ( Chen et al, 2017 ) and in vivo . However, the potential targets and pharmacological mechanism underlying the regulation of DMDD in lung cancer tumorigenesis still remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The anticancer effects of natural products and their secondary metabolites are widely used in the treatment of tumors, including paclitaxel, vincristine, etoposide and camptothecin ( Ouyang et al, 2014 ). 2-dodecyl-6-methoxycyclohexa-2, 5-diene-1,4-dione (DMDD), an active quinonoids from the roots of Averrhoa carambola L. , exhibits various biological effects, including antidiabetic ( Kintoko et al, 2018 ), antidiabetic nephropathy ( Lu et al, 2019 ) and anti-breast cancer ( Gao et al, 2015 ; Chen et al, 2017 ; Zhou et al, 2020 ) activities. The various biological activities and low toxicity of DMDD make it a promising candidate for clinical development.…”
Section: Introductionmentioning
confidence: 99%
“…Pre-treatment with MAPK inhibitors reduced the protein expression of Bax promoted by IL-1α in the MC3T3-E1 cells, suggesting the significance of JNK and the p38 MAPK signaling in modulating IL-1α-induced apoptosis and osteoblast differentiation of MC3T3-E1 cells [ 30 ]. In addition, phosphorylation of JNK leads to an increase in apoptosis rate in cells under different conditions, such as ischemia-reperfusion [ 31 , 32 ], cancers [ 33 , 34 ], and liver injury [ 35 ]. Moreover, miR-214 inhibitor significantly decreased the expression of ALP, OCN, and RUNX2, as well as ALP activity in MC3T3-E1 cells, which was enhanced by additional treatment with SP600125, a JNK inhibitor [ 36 ].…”
Section: Discussionmentioning
confidence: 99%